Ensaios em economia Kaldoriana - SILVA, Sérgio Felipe Melo da (Universidade Federal do Pará, 2024)
This doctoral thesis is structured into three essays, arranged in three chapters, and deals with Kaldorian Economics in relation to other theoretical approaches and applications using input-output analysis. The first essay seeks to establish a theoretical connection between the ideas of economists Nicholas Kaldor and Giovanni Dosi, based on an analysis of the regional production technological structure using the input-output methodology created by Wassily Leontief. This approach is applied to the economy of the Legal Amazon (Brazil), specifically the state of Pará. The preliminary application of the Kaldor-Dosi perspective, with the help of the Leontief input-output matrix, allowed for specific conclusions to be drawn about the dynamics of the mineral extraction industry in relation to the productive structure of the state of Pará. The second essay focuses primarily on structural change, which arises from theories of economic development from various theoretical schools, mainly linked to the manufacturing industry. The essay proposes its own approach, called complexity with an evolutionary approach, which results from the connection between distinct theoretical approaches, namely the Kaldorian approach, based on Kaldor's Laws, the Neo-Schumpeterian approach, also called evolutionary, especially the theory of technological paradigms and trajectories, and the approach of economic complexity. The methodology used is structural decomposition analysis, which is a technique within the framework of the input-output methodology. The third essay seeks to identify the systemic importance of the industries of the Manaus industrial complex and, thus, the Amazonian manufacturing industry in the economy of the Amazon region and the rest of Brazil. This is done through a theoretical approach that relates the interregional perspective to Kaldor's Laws in the discussion of economic development. The theoretical aspect of this article is the approach of Kaldor's Laws combined with the assumptions of Regional Economics from an interregional perspective and the approach of technological innovations. It is understood that the forces that operate in the interregional dynamics are also determinants to explain the movements of economic performance of a region or country. The methodological apparatus is input-output analysis, through the hypothetical extraction technique.